تحسين فعالية إدارة المخاطر في ظل تطبيق المداخل الحديثة للرقابة المصرفية ـ دراسة تحليلية في المصرف العقاري السوري ـ - حبيب سمر (Latakia University Journal - Economic and Legal Sciences Series, 2014)
على الرغم من التطور الحاصل في بيئة عمل المصارف في القرن الحادي والعشرين، ومع توسع الأنشطة والعمليات المصرفية تزايد تعرضها للعديد من المخاطر (مخاطر ائتمانية، مخاطر السوق ، مخاطر التشغيل...) والتي تحتاج بدورها إلى إدارتها بصورة دقيقة وشاملة بما يضمن الحفاظ على استقرار وسلامة ومتانة عمل المصارف وتجنب الوقوع في مخاطر الفشل إلى أقصى حد ممكن، الأمر الذي يستلزم ضرورة الالتزام بمعايير الرقابة المصرفية والتي تعتبر الضمانة لسلامة العمل المصرفي، ويسهم استخدام المداخل الحديثة (مدخل التصنيف الداخلي – المدخل المعياري – مدخل القياس المتقدم ) بما تتضمنه من متطلبات كمية ونوعية في تحسين فعالية إدارة المخاطر ، وفي هذه الدراسة تم التركيز على الدور الذي تسهم فيه المداخل الحديثة في تحسين فعالية إدارة المخاطر في المصرف العقاري السوري،وعلى اعتبار أن مديرية إدارة المخاطر محدثة خلال السنوات القليلة الماضية فهي بحاجة إلى التقييد بمعايير الرقابة المصرفية والتي تعتبر المداخل الحديثة من أحد أدواتها الأمر الذي سوف ينعكس على تطوير عملية إدارة المخاطر المختلفة ويحقق تغييراً جوهرياً في الحد منها وتجنبها لأن منع حدوثها قد لا يكون ممكناً باعتبار أن جانباً منها مرتبط بعوامل خارجية واقتصادية وظروف البيئة المحيطة بعمل المصرف، وقد اعتمدت الدراسة على المنهج الوصفي التحليلي وإجراء المقابلات مع العاملين في مديرية المخاطر للتعرف على آلية عمل المديرية وما يمكن أن تحققه في حال اعتمادها على تطبيق المداخل الحديثة ، وتوصلت الدراسة إلى أن ما تقوم به المديرية يقع ضمن إطار تطبيق مدخل التصنيف الداخلي وانها بحاجة إلى الالتزام بمعايير الرقابة المصرفية بما يضمن زيادة فعاليتها فيما يخص مختلف أنواع المخاطر. Despite the development of work environment at banks in the twenty-first century, and with the expansion of activities and banking operations, these banks have increasing risks (credit risk, market risk, operational risk, etc.) which in turn need to be managed more accurately and comprehensively to ensure maintaining stability, safety, and durability of the work of banks, and avoiding the risk of failure to the maximum extent possible. This requires the need to adhere to the standards of banking supervision, which is the guarantee for the safety of the banking business and using modern inputs (the internal rating input, the standard input, the Advanced Measurement input). In addition, the provisions of the requirements of quantity and quality contribute to improving the efficiency of Risk Management. In this study, the focus is on the role that modern inputs play in improving the efficiency of risk management in the Real Estate Bank of Syria, given that the Directorate of Risk Management have been updated over the past few years, they need to meet the restriction standards of banking supervision, which considers modern inputs one of its tools. This will be reflected on the development of the risk management process and achieve various fundamental changes in reducing the risks, because preventing them may not be possible considering that one aspect of which is linked to external and economic factors, and the environmental conditions surrounding the work of the bank. This study is based on the descriptive analytical method, and conducts interviews with employees in the Directorate of risks to identify the mechanism of action taken by the Directorate and what can be achieved if it depends on the application of modern inputs. This research shows that what the Directorate are doing falls within the framework of the application of the input to the internal rating, and they need to adhere to the standards of banking supervision in order to increase their efficiency in relation to various types of risks.